Domestic Moral Agency among Elderly Learners through Al-Muhasibi’s Practical Sufism - Yogi Prana Izza Izza; Nur Fadhilah; Tata Ilmi Ma'una; Intan Nur Maulida; Ziaulrahman Mushkalamzai Mushkalamzai (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Amid increasing concerns over moral degradation within contemporary Muslim families, the educational role of elderly Muslims in transmitting Islamic moral values through everyday domestic life has received limited scholarly attention. Therefore, this study aims to explore how elderly learners internalize the ethical teachings of Haris al-Muhasibi’s Risalah al-Mustarsyidin and transform them into forms of domestic moral agency within Muslim families. Employing a qualitative approach with Interpretative Phenomenological Analysis (IPA), this research involved elderly participants from the Saturday Morning Islamic Study (KISM), a non-formal Islamic learning community in East Java, Indonesia. Data were collected through in-depth interviews, participant observation, and field notes. The findings reveal that practical Sufism operates as a form of domestic moral pedagogy through role modelling, worship supervision, peer mentoring, cultural da'wah, and ethical communication that collectively strengthen family religiosity and intergenerational moral transmission. Rather than functioning solely as personal spiritual discipline, muhasabah is interpreted as a pedagogical practice shaping everyday interpersonal ethics within the household. The study further identifies elderly learners as “micro-mursyid” figures who exercise informal religious authority by transmitting Islamic values through ordinary family interactions. These findings contribute to contemporary discussions of practical Sufism by extending its significance beyond individual spirituality toward domestic moral agency and informal Islamic education in contemporary Muslim society.